IMPROVING STUDENTS’ LISTENING COMPREHENSION BY TEACHING CONNECTED SPEECH - Siti Musfirah; Khairil Razali; Yuliar Masna (Universitas Islam Negeri Banda Aceh, 2019)
This present research was conducted in order to find out the improvement in students’ listening comprehension and to figure out whether students’ interest in listening class increases after being taught the aspects of connected speech. This research used a quantitative method with pre-experimental design, namely pre-test post-test involving only the experiment group. The population of this research was all the students of the eleventh-grade who are studying at MAS Darul Ihsan which amount to 184 students. In addition, the sample of this research was 30 students of class XI F that was chosen using purposive sampling. Moreover, this research used pre-test and post-test as well as questionnaires as data collection instruments. The research found that teaching connected speech in the listening classroom improved students’ listening comprehension. This was indicated by the comparison of t-score which is higher than t-table, (3.61 > 2.04). Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Furthermore, the result of students’ response sheets indicated that students have positive perception toward the teaching connected speech and it can increase their interest in learning listening.